39.9k views
1 vote
This is calculus

using L'hospitals rule
Lim x --> 0 (1+2x)^(-3/x)

User Adardesign
by
4.3k points

1 Answer

3 votes

De l'Hospital rule applies to undetermined forms like


(0)/(0),\quad(\infty)/(\infty)

If we evaluate your limit directly, we have


\displaystyle \lim_(x\to 0)(1+2x)^{-(3)/(x)} = 1^\infty

which is neither of the two forms covered by the theorem.

So, in order to apply it, we need to write the limit as follows: we start with


f(x)=(1+2x)^{-(3)/(x)}

Using the identity
e^(\log(x))=x, we can rewrite the function as


f(x)=e^{\log\left((1+2x)^{-(3)/(x)}\right)}

Using the rule
\log(a^b)=b\log(a), we have


f(x)=e^{-(3)/(x)\log(1+2x)}

Since the exponential function
e^x is continuous, we have


\displaystyle \lim_(x\to 0) e^(f(x)) = e^{\lim_(x\to 0) f(x)}

In other words, we can focus on the exponent alone to solve the limit. So, we're focusing on


\displaystyle \lim_(x\to 0) -(3)/(x)\log(1+2x)

Which we can rewrite as


\displaystyle \lim_(x\to 0) -(3)/(x)\log(1+2x) = -3\lim_(x\to 0)(\log(1+2x))/(x)

Now the limit comes in the form 0/0, so we can apply the theorem: we derive both numerator and denominator to get


\displaystyle -3\lim_(x\to 0)(\log(1+2x))/(x) = -3 \lim_(x\to 0)((2)/(1+2x))/(1) = -3\cdot 2 = -6

So, the limit of the exponent is -6, which implies that the whole expression tends to


e^(-6)=(1)/(e^6)

User Jay Shah
by
4.7k points